Saint Mazie : a novel - Attenberg, Jami (Grand Central Publishing, 2015)
"Meet Mazie Phillips: big-hearted and bawdy, she's the truth-telling proprietress of The Venice, the famed New York City movie theater. It's the Jazz Age, with romance and booze aplenty--even when Prohibition kicks in--and Mazie never turns down a night on the town. But her high spirits mask a childhood rooted in poverty, and her diary, always close at hand, holds her dearest secrets. When the Great Depression hits, Mazie's life is on the brink of transformation. Addicts and bums roam the Bowery; homelessness is rampant. If Mazie won't help them, then who? When she opens the doors of The Venice to those in need, this ticket-taking, fun-time girl becomes the beating heart of the Lower East Side, and in defining one neighborhood helps define the city. Then, more than ninety years after Mazie began her diary, it's discovered by a documentarian in search of a good story. Who was Mazie Phillips, really? A chorus of voices from the past and present fill in some of the mysterious blanks of her adventurous life. Inspired by the life of a woman who was profiled in Joseph Mitchell's classic Up in the Old Hotel, SAINT MAZIE is infused with Jami Attenberg's signature wit, bravery, and heart. Mazie's rise to "sainthood"--and her irrepressible spirit--is unforgettable"--